85.6k views
2 votes
at is another way to write the expression ​ p⋅(10−2) ​ ? (10⋅2)−p 10⋅2−p (10⋅2)⋅p (p⋅10)−(p⋅2)

User Jmr
by
5.1k points

1 Answer

0 votes

Answer:

(p ⋅ 10) − (p ⋅ 2)

Explanation:

Try to substitute "p" with any number.

Let's say p = 2

So

p ⋅ (10 − 2)

2 ⋅ (10 − 2)

2 ⋅ (8)

= 16

Now for the other equations

(p ⋅ 10) − (p ⋅ 2)

(2 ⋅ 10) − (2 ⋅ 2)

(20) - (4)

= 16

(10 ⋅ 2) − p

(10 ⋅ 2) − 2

(20 ) − 2

= 18

10 ⋅ 2 − p

10 ⋅ 2 − 2

20 - 2

= 18

(10 ⋅ 2) ⋅ p

(10 ⋅ 2) ⋅ 2

(20) ⋅ 2

= 40

Only (p ⋅ 10) − (p ⋅ 2) has the same result as p ⋅ (10 − 2).

Cheers

User PeterJames
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.